Survival After Hip Fracture: A Comparative Analysis Between a Private and a Public Health Center in Chile - Barahona, Maximiliano (Cureus, 2020)
Purpose The purpose of the study is to compare the survival after hip fracture in patients older than 50 years after hip fracture between a private and a public health center in Chile. We hypothesize that treatment at a private health center (PRH) may be associated with lower one-year mortality and longer median survival time after hip fracture (adjusted by gender and age) compared to a public health center (PLH). Methods PRH and PLH patients who were coded with a diagnosis of hip fracture were included in this study. PRH patients were included between 2002 to 2018, and PLH patients were included from 2012 to 2018. One-year mortality was estimated by logistic regression; meanwhile, median survival time was estimated by exponential regression. A survival analysis study was designed and approved by our institutional ethics review board. Results A total of 2130 patients were included in the PLH cohort, and a total of 1110 patients were included in the PRH. The one-year mean mortality, adjusted by age and gender, was 0.23 (range: 0.21 to 0.25) in the PLH and 0.16 (range: 0.13 to 0.18) in the PRH cohort. The median survival time, adjusted by age and gender, was 4.2 years (range: 4.1 to 4.4) in the PLH and 6.8 years (range: 6.3 to 7.29) in the PRH cohort. Conclusion Patients older than 50 years treated in a private health center have a higher median survival time and a lower probability of dying one year after a hip fracture.